THE CONTRIBUTION OF STUDENT STUDENT INTERPERSONAL SKILL DEVELOPMENT AT ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Muhammad Haqqi Riyansyah (PBI 15 UMY 034, 2015)
*34 Learning and teaching can be defined as transferring information and knowledge to reach learning goal in the classroom. Delivering teaching and learning process needs an approach. Mostly, approach that is used in the class is an approach that is centered to lecturer. In this approach, lecturer explains the materials in front of the class and students only listen to that explanation. Based on researcher’s experience, students who are talkative in class would be limited to share their ideas in front of class because of using this classical approach. Hence, interpersonal skills such as communication, leadership, public speaking and teamwork could be possibly trained by using proper approach. Student-centered learning could be a solution by giving contribution in developing student interpersonal skills. Additionally, according to the background of this study, researcher was interested to do the research about description of the contribution that studentcentered learning gave to develop student interpersonal skills at EED of UMY. In this research, there are three research questions: (1) How is the implementation of student-centered learning of English Education Department of Universitas Muhammadiyah Yogyakarta? (2) What are interpersonal skills developed at English Education Department of UMY? (3) What is the contribution of studentcentered learning for student interpersonal skills development at EED of UMY?. Furthermore, there are three aims of this research: (1) To find out the implementation of the student-centered learning at English Department of UMY (2) To find out the three students interpersonal skill developed at English Education Department of UMY (3) To find out the contribution of studentcentered learning for student interpersonal skill development at English Education Department of UMY. This research used qualitative design to gain the data. Besides, in answering three research questions, researcher did interview with three students of class A, B, C from batch 2012 especially in class of Research Method in which used student centered learning approach. Moreover, researcher chose the participants based on good score soft skill and also recommendation from the related lecturer. All the data had been transcribed and categorized by Weft Qualitative Data Analysis (QWDA). The result is that student-centered learning had been completely implemented at EED of UMY. Then, student interpersonal skills developed here were speaking skill, communication skill, teamwork skill and leadership skill based on the characteristics appeared. Furthermore, those skills were entirely developed because of the contribution of student-centered learning in the process of teaching and learning in the classroom.